Visualization of DNA-containing structures in various species of Chlorophyta, Rhodophyta and Cyanophyta using SYBR Green I dye - Vítová, M; Hendrychová, J; Cepák, V; Zachleder, V (Folia microbiologica, 2005)
We developed an alternative method of staining cell nuclei and chloroplast nucleoids of algal cells using SYBR Green I (the fluorescent dye used commonly for detecting dsDNA in agarose and polyacrylamide gels as an alternative to highly mutagenic ethidium bromide and for DNA staining of viruses and bacteria followed by flow cytometry, digital image analysis or real-time PCR), which enabled routine staining in vivo. Cells do not need to be fixed or treated chemically or physically before staining, thus the shape, size and position of DNA-containing structures are not affected. The fluorescence signal is sharp and reproducible. Examples of application of the method are shown in color microphotographs for representatives of eukaryotic algae from the taxa Chlorophyta, Rhodophyta and the prokaryotic Cyanophyta. The method is also useful for studying progress of the cell cycle in algal cells dividing by multiple fission, as shown by observation of changes in nuclear number during the cell cycle of the green alga Chlamydomonas reinhardtii and Scenedesmus quadricauda. Staining with SYBR Green I can be recommended as a fast, safe and efficient method for the detection of DNA-containing structures in vivo.
Keywords: Chlorophyta; Rhodophyta; Cell Cycle; DNA, Algal; Diamines; Benzothiazoles; permeabilita buněčné membrány; Quinolines; DNA řas; počítačové zpracování obrazu; barvení a značení; Image Processing, Computer-Assisted; reprodukovatelnost výsledků; sinice; benzothiazoly; fluorescenční barviva; Fluorescent Dyes; Flow Cytometry; Reproducibility of Results; Cell Membrane Permeability; organické látky; Organic Chemicals; polymerázová řetězová reakce; Polymerase Chain Reaction; diaminy; průtoková cytometrie; Cyanobacteria; buněčný cyklus; Staining and Labeling; chinoliny